The radiative association of PO/PH+ and the photodissociation of PH+ - Chen, Yang; Lin, Xiaohe; Xiao, Lidan; Li, Zijian; Zhang, Songbin; Cheng, Yongjun; Wu, Yong; Yan, Bing (Frontiers in Astronomy and Space Sciences, 2024)
The potential energy curves (PECs) and transition dipole moments (TDMs) of PH+ and PO are computed with multireference configuration interaction method. And the cross sections for the radiative association (RA) of PH+ and PO, which in the most efficient way to form the ground states, are presented via quantum mechanical theory (QM) and computed ab initio molecular data. The thermal rate coefficients are also expressed and fitted with the standard formula: k(T)=A(T/300)^α e^(-β/T) in the range of 10K - 15000K. Meanwhile, the photodissociation that is the inverse process of RA for PH+ is also studied, including eight photodissociation channels for the computation of state-resolved cross sections. Careful comparisons with the Leiden Observatory database are made. Considering the cross sections above, the local thermodynamic equilibrium cross sections at the temperatures of 0, 500, 1000 and 2000K are also shown. We expect the results helpful for studies of the phosphorus chemistry in interstellar medium and planetary atmospheres.P